KINERJA PERDAGANGAN SERTA STRATEGI EKSPOR PRODUK-PRODUK PHARMACEUTICAL DAN KOSMETIK BERBASIS HERBAL INDONESIA DI PASAR DUNIA - Reni K. Arianti; . Hasni (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2010)
Industrial development of herbal medicine, cosmetics and health foods in Indonesia today has grown substantially. utilization of natural resources, especially of medicinal species, will continue, in connection with the Indonesian nation strong linkages to the cultural tradition of using traditional medicine. This trend has extended to the whole world and is known as the “new green wave” or a lifestyle trend “back to nature”. Indonesia as one giant center (mega center) biodiversity, but only about 600 species of plants, 1000 species of animals and 1000 species of microorganism that has been known and utilized by the community potential. Indonesia has a high potential for use as a commercial industry development of herbal medicine, cosmetics and health-oriented food exports. Pharmaceutical and cosmetic products based on herbal Indonesia during the last five years (2003-2007) of each export growth average of 7.1 % and 16.9 % per year. Share growth of Indonesian herbal-based pharmaceutical products in the world market is only 3.9 % per year while the world market demand grew 15.5 % per year, while the share of Indonesian herbal cosmetics in the world market and 13.5% of world market demand grew 13.1 % .The structure of the herbal pharmaceutical products exported Indonesia to the world market has not been in line with the structure of product demand in world markets .Indonesian exports more the form of herbal ingredients than finished products (drug/cosmetics), while the world market demand be seen otherwise. This opens the opportunity for Indonesia to expand its market in the world. To be able to take advantage of existing opportunities, Indonesia needs to have effective strategies, such as Indonesia needs to focus on products that have a cluster “Natural Beauty”, the increase in value added herbal products, switching technology, raw material processing, the application of standard CPOTB with mentoring programs, vertical integration with industry in the importing countries will support the cosmetic raw material export activities, information provision and promotion of sustainable export of herbal products.